THE VALUES OF ISLAMIC EDUCATION IN THE STORY OF IBRAHIM P.B.U.H (Analysis Of Chapter Al-An'am Verses 74-81 And Chapter Al-Anbiyâ 51-70). - Rahman Sutomo, Syamsu Nahar , Abdullah AS (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2019)
Abstrak: The purpose of this study is to examine the content of Islamic education values in the story of Prophet Ibrahim As in chapter Al-an'am verses 74 to 81 and chapter Al-Anbiyâ verses 51 to 70. Both stories have a thematic relationship from the message they carry. If at chapter Al-an'am verses 74-81, Prophet Ibrahim p.b.u.h found the presence of God by observing the signs in nature then in chapter Al-Anbiyâ verse 51-70, the prophet Ibrahim p.b.u.h conveyed instructions about the presence of God to his people by means of discussion to his people. The methodology used in the study is the Library Study Method. This research belongs to the literature study using the method of content analysis with the Tahlili Method. There is also the research method used is the method of interpretation of the maudhu'i, namely the method of interpreting the Qur'an thematically by summarizing the verses of the Koran that are relevant to the values of education to be studied. The data sources used in this study are the Qur'anic translation of the Ministry of Religion of the Republic of Indonesia, the exegesis of Ibn Kathir, the exegesis of Muhammad Quraiys Shihab al-Misbah, the exegesis of Muhammad Mutawalli Sya'rawi and the exegesis of Fi Zilal Quran sayyid qhutub. The results of this study show the values of Islamic education in the aspects of Aqidah, the story of Prophet Ibrahim p.b.u.h in the chapter Al-an'am verses 74-81 teaches the values of true Aqeedah as follows: 1. The value of Aqeedah. Almighty Allah will not have the "drowning" nature which means that he will not leave his creatures and supervising will always be there for his creatures, Allah will give guidance to His creatures, Allah is the Almighty so that Allah is not equal. 2. Moral values. Morals to Allah (habluminallah): if Allah gives instructions to his servant and answers prayers, then it is an obligation for His servants to accept His instructions and guidance and not obey them. While the values of Islamic education in the story of the prophet Ibrahim p.b.u.h in Al-Anbiyâ chapter verses 51-70, are as follows: 1. The value of Aqeedah, Idols are not worthy of being considered gods because they cannot protect themselves from being destroyed so how can idols protect the devotee. Idols cannot even tell who has destroyed him so that the idol itself cannot also guide his devotee, 2. The Value of Ukhuwah, Morals displayed in the story of Prophet Ibrahim p.b.u.h are noble morals both in the face of his infidel father and facing his people infidel He was not hostile to his father and even prayed for his father. He invited his people to dialogue in conveying the truth. The value of ukhuwah here is ukhuwah insaniyah, 3. The educational value of discussion, Prophet Ibrahim p.b.u.h in conveying the truth and rectifying the mistakes of his people in worship by means of dialogue using logic and persuasive style.Keywords: Chapter Al-An'am, Chapter Al-Anbiyâ, Prophet Ibrahim P.B.U.H, Values, Education, Aqidah, Akhlak, Ukhuwah